Multicolor luminescent material based on interaction between TiNbO5- nanosheets and lanthanide ions for visualization of pH change in inorganic gel electrolyte - Awaya, Keisuke; Iso, Kei-Ichiro; Ida, Shintaro (Nanoscale, 2022)
Layered nanosheet materials showing a drastic luminescence change in response to changes in proton concentration (pH) were prepared by sandwiching Eu3+ and Tb3+ cations with anionic TiNbO5- nanosheets using electrostatic interaction. Each trivalent lanthanide ion showed a different response to pH change: a strong red emission from Eu3+ was observed at low proton concentrations (pH: 13) and a green emission from Tb3+ was dominant at high proton concentrations (pH: 1). The photoluminescence intensity was determined by the balance between the photocatalytic activity of TiNbO5- nanosheets and energy transfer from the host layer to the guest lanthanide ions. Moreover, the trivalent lanthanide/TiNbO5- nanosheet hybrid formed a gel-like solid in aqueous solution, which functioned as an inorganic gel electrolyte when mixed with Na2SO4. The multicolor luminescence (red-yellow-green) of the lanthanide/TiNbO5- nanosheet hybrid enabled direct visualization of the diffusion of protons in an inorganic gel electrolyte during water electrolysis.Layered nanosheet materials showing a drastic luminescence change in response to changes in proton concentration (pH) were prepared by sandwiching Eu3+ and Tb3+ cations with anionic TiNbO5- nanosheets using electrostatic interaction. Each trivalent lanthanide ion showed a different response to pH change: a strong red emission from Eu3+ was observed at low proton concentrations (pH: 13) and a green emission from Tb3+ was dominant at high proton concentrations (pH: 1). The photoluminescence intensity was determined by the balance between the photocatalytic activity of TiNbO5- nanosheets and energy transfer from the host layer to the guest lanthanide ions. Moreover, the trivalent lanthanide/TiNbO5- nanosheet hybrid formed a gel-like solid in aqueous solution, which functioned as an inorganic gel electrolyte when mixed with Na2SO4. The multicolor luminescence (red-yellow-green) of the lanthanide/TiNbO5- nanosheet hybrid enabled direct visualization of the diffusion of protons in an inorganic gel electrolyte during water electrolysis.